1999
DOI: 10.1007/s001340050813
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status in patients with acute respiratory distress syndrome

Abstract: The antioxidative system is severely compromised in patients with ARDS. Plasma levels of alpha-tocopherol, ascorbate, beta-carotene and selenium are decreased. Elevated MDA levels provide further evidence of massive oxidative stress. The routine replacement of micronutrients according to recommended daily allowances was inadequate to compensate for the increased requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
162
0
9

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(175 citation statements)
references
References 21 publications
4
162
0
9
Order By: Relevance
“…Extensive literatures have boasted the essential role of oxidative stress in the development of OA-induced ALI. [38][39][40][41] Intravenous administration of OA could produce neutrophil activation as well as endothelium damage, resulting in abundant ROS generation and decreased activity or protein expression of SOD and catalase probably through downregulation of NADPH oxidase-dependent pathway or upregulation of NF-kB phosphorylation at p65. [42][43][44][45] Thus, we designed in vitro and in vivo experiments to investigate the possible impact of SO 2 pathway on lung tissue oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literatures have boasted the essential role of oxidative stress in the development of OA-induced ALI. [38][39][40][41] Intravenous administration of OA could produce neutrophil activation as well as endothelium damage, resulting in abundant ROS generation and decreased activity or protein expression of SOD and catalase probably through downregulation of NADPH oxidase-dependent pathway or upregulation of NF-kB phosphorylation at p65. [42][43][44][45] Thus, we designed in vitro and in vivo experiments to investigate the possible impact of SO 2 pathway on lung tissue oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has established that ARDS increases oxidative stress and secretion of ROS from the neutrophils of patients (25)(26)(27)(28)(29)(30). Studies involving the experimental induction of ALI as a model for ARDS have reported increased MDA concentration, indicating increased oxidative stress and altered activity of antioxidant enzymes (15,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving the experimental induction of ALI as a model for ARDS have reported increased MDA concentration, indicating increased oxidative stress and altered activity of antioxidant enzymes (15,(31)(32)(33). Additional research has revealed that the plasma of patients with ARDS contains reduced levels of antioxidants and that neutrophil infiltration and ROS accumulation can exhaust the total antioxidant capability of the lungs (26,30).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma antioxidant levels decreased in patients with ARDS. Free oxygen radicals and neutrophile streams are thought to consume the total antioxidant capacity of lungs (3,4).…”
Section: Effects Of Lycopene On the Model Of Oleic Acid-induced Acutementioning
confidence: 99%